De novo synthesis of benzenoid compounds by the yeast hanseniaspora vineae increases the flavor diversity of wines - Martín, Valentina (2016)
Benzyl alcohol and other benzenoid-derived metabolites of particular importance in plants confer floral and fruity flavors to wines. Among the volatile aroma components in Vitis vinifera grape varieties, benzyl alcohol is present in its free and glycosylated forms. These compounds are considered to originate from grapes only and not from fermentative processes. We have found increased levels of benzyl alcohol in red Tannat wine compared to that in grape juice, suggesting de novo formation of this metabolite during vinification. In this work, we show that benzyl alcohol, benzaldehyde, p-hydroxybenzaldehyde, and p-hydroxybenzyl alcohol are synthesized de novo in the absence of grape-derived precursors by Hanseniaspora vineae. Levels of benzyl alcohol produced by 11 different H. vineae strains were 20-200 times higher than those measured in fermentations with Saccharomyces cerevisiae strains. These results show that H. vineae contributes to flavor diversity by increasing grape variety aroma concentration in a chemically defined medium. Feeding experiments with phenylalanine, tryptophan, tyrosine, p-aminobenzoic acid, and ammonium in an artificial medium were tested to evaluate the effect of these compounds either as precursors or as potential pathway regulators for the formation of benzenoid-derived aromas. Genomic analysis shows that the phenylalanine ammonia-lyase (PAL) and tyrosine ammonia lyase (TAL) pathways, used by plants to generate benzyl alcohols from aromatic amino acids, are absent in the H. vineae genome. Consequently, alternative pathways derived from chorismate with mandelate as an intermediate are discussed.